Clinical evaluation of a novel urinary protein competitive immunoassay in the detection of proteinuria in adults with sickle cell disease - Vincent Boima; Yvonne Dei-Adomako; Margaret Lartey; Akosua Asante-Offei; Markus Warlitz; Donald Very (Frontiers in Medicine, 2026)
Background Sickle cell disease (SCD) affects millions of people worldwide and causes proteinuric kidney diseases. Early detection of proteinuria in patients with SCD would allow for earlier intervention, possibly limiting renal complications. Here, we report the results of a case-control, proof-of-concept study to assess the clinical performance of a novel urine protein immunoassay (UP immunoassay) for detecting small molecular weight proteins in the urine of patients with sickle disease (SCD) and healthy volunteers. Methods This study recruited 100 patients with SCD (50 with proteinuria and 50 without) and 50 healthy controls without SCD or proteinuria. Patient demographic information and early morning urine specimens were collected. The samples were tested for proteinuria using the UP immunoassay and clinical laboratory tests for albumin and creatinine levels. Albumin: creatinine (ACR) and UP:creatinine (UPCR) ratios were calculated and compared across groups. Results Of the 150 recruited participants, 147 completed the study. Our results demonstrated that the UPCR and ACR were substantially equivalent in the clinical detection of proteinuria across all patient groups. Despite this equivalence, the UPCR and ACR values did not correlate in the 147 patient samples tested (R 2 = 0.5,113). Conclusion UPCR measurement is clinically useful and equivalent to ACR measurement for detecting proteinuria across the three subject groups. The moderate correlation between the UPCR and ACR suggests that the UP immunoassay detects a collection of non-albumin proteins and peptides.